Kolaborasi atau Mandiri? Analisis Peran Work Self-efficacy terhadap Job Crafting pada Karyawan di Indonesia - Anugrah, Nazir Ultama; Yudhaningrum, Lupi; Haryono, Khairina Widya Primandari; Lubis, Irma Rosalinda; Eryanfarros, Raffi (Universitas Mercu Buana, 2025)
This study aims to determine the influence of work self-efficacy on job crafting among employees. Work self-efficacy refers to an individual's belief in their ability to complete work tasks, while job crafting is the effort employees make to adjust their work to better suit their needs and capabilities. This research employed a quantitative approach with a correlational design. The respondents consisted of 351 employees in Indonesia who had been working for at least one year. The instruments used were the Job Crafting Scale (JCS) and the Occupational Self-Efficacy Scale (OSS). Data analysis was conducted using simple linear regression. The results showed a significant influence of work self-efficacy on job crafting (p = 0.001) with an R² of 0.454. This indicates that work self-efficacy contributes 45.4% to job crafting. In conclusion, the higher the work self-efficacy possessed by employees, the higher the job crafting behavior demonstrated in their work. These findings have important implications for organizational practice in developing employee adaptation and flexibility through strengthening work self-efficacy, especially in the face of dynamic environmental changes.